Catalytic Lignin Valorization Process for the Production of Aromatic Chemicals and Hydrogen - Zakzeski, Joseph; Jongerius, Anna L.; Bruijnincx, Pieter C. A.; Weckhuysen, Bert M. (ChemSusChem, 2012)
With dwindling reserves of fossil feedstock as a resource for chemicals production, the fraction of chemicals and energy supplied by alternative, renewable resources, such as lignin, can be expected to increase in the foreseeable future. Here, we demonstrate a catalytic process to valorize lignin (exemplified with kraft, organosolv, and sugarcane bagasse lignin) using a mixture of cheap, bio‐renewable ethanol and water as solvent. Ethanol/water mixtures readily solubilize lignin under moderate temperatures and pressures with little residual solids. The molecular weight of the dissolved lignins was shown to be reduced by gel permeation chromatography and quantitative HSQC NMR methods. The use of liquid‐phase reforming of the solubilized lignin over a Pt/Al2O3 catalyst at 498 K and 58 bar is introduced to yield up to 17 % combined yield of monomeric aromatic oxygenates such as guaiacol and substituted guaiacols generating hydrogen as a useful by‐product. Reduction of the lignin dissolved in ethanol/water using a supported transition metal catalyst at 473 K and 30 bar hydrogen yields up to 6 % of cyclic hydrocarbons and aromatics. A catalytic approach to valorize lignin by using a mixture of cheap, biorenewable ethanol and water as solvent is reported. Liquid‐phase reforming of the solubilized lignin over Pt/Al2O3/co‐catalyst yields monomeric aromatic oxygenates and hydrogen as a useful byproduct. The solvated lignin can also be subjected to a subsequent conversion step, for example, using an appropriate reduction catalyst and hydrogen to yield a different slate of hydrocarbons and aromatics.